2016
DOI: 10.1073/pnas.1610379113
|View full text |Cite
|
Sign up to set email alerts
|

Terpene synthase genes in eukaryotes beyond plants and fungi: Occurrence in social amoebae

Abstract: Terpenes are structurally diverse natural products involved in many ecological interactions. The pivotal enzymes for terpene biosynthesis, terpene synthases (TPSs), had been described only in plants and fungi in the eukaryotic domain. In this report, we systematically analyzed the genome sequences of a broad range of nonplant/ nonfungus eukaryotes and identified putative TPS genes in six species of amoebae, five of which are multicellular social amoebae from the order of Dictyosteliida. A phylogenetic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 37 publications
(37 reference statements)
1
95
0
5
Order By: Relevance
“…However, mounting evidence suggests that microbes, and especially bacteria, emit diverse volatile compounds with significant biological activities on a wide range of target organisms, including plants and their pathogens (Groenhagen et al , ; Piechulla et al , ). Although plant‐associated fungi and protists also emit volatile organic compounds (Hung et al , ; Chen et al , ; Li et al , ), the present review focuses on bacterial volatiles and highlights the diverse means by which these compounds contribute to maintaining and protecting plant health.…”
Section: Introductionmentioning
confidence: 99%
“…However, mounting evidence suggests that microbes, and especially bacteria, emit diverse volatile compounds with significant biological activities on a wide range of target organisms, including plants and their pathogens (Groenhagen et al , ; Piechulla et al , ). Although plant‐associated fungi and protists also emit volatile organic compounds (Hung et al , ; Chen et al , ; Li et al , ), the present review focuses on bacterial volatiles and highlights the diverse means by which these compounds contribute to maintaining and protecting plant health.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated number of 75,000 different compounds are known from all kinds of organisms including plants [1], bacteria [25], fungi [6] and, as recently shown, even social amoebae [7]. These molecules are all made from only a handful of linear and achiral precursors such as geranyl diphosphate (GPP, monoterpenes), farnesyl diphosphate (FPP, sesquiterpenes) and geranylgeranyl diphosphate (GGPP, diterpenes).…”
Section: Introductionmentioning
confidence: 99%
“…They are best known to humans as plants metabolites. However, recent studies revealed that terpenes can be produced by all kingdoms of life including prokaryotes (Takamatsu et al 2011;Yamada et al 2012;Yamada et al 2015;Song et al 2015b;Chen et al 2016). Recently, Yamada et al (2015) described a powerful bioinformatics method based on the use of Hidden Markov Models (HMMs) and Protein Families Database (PFAM) search that has allowed the discovery of terpene synthases of bacterial origin and showed that phylogenetically different bacteria can be a rich source of terpenes.…”
Section: Chapter 2 33mentioning
confidence: 99%
“…In this context, terpenes as one of the largest and most diverse class of metabolites that are produced by all kingdom of live including bacteria, fungi and plants (this thesis; Yamada et al 2015;Chen et al 2016) seem to play important roles in many soil processes (Chapter 2). For instance, terpene-mediated interactions can contribute to the suppression of soil-borne plant diseases (Song et al 2015b; Chapter 6), stimulation of plant growth (Minerdi et al 2011), soil nutrient cycles (Kleinheinz et al 1999;Owen et al 2007; Chapter 3), or the connection of soil food webs (Chapter 4).…”
Section: The Role Of Volatile Mediated Interactions In Ecosystem Funcmentioning
confidence: 99%
See 1 more Smart Citation